Modeling and Implementation of a Power Estimation Methodology for SystemC - Matthias Kuehnle; Andre Wagner; Alisson V. Brito; Juergen Becker (International Journal of Reconfigurable Computing)
This work describes a methodology to model power consumption of logic modules. A detailed mathematical model is presented and incorporated in a tool for translation of models written in VHDL to SystemC. The functionality for implicit power monitoring and estimation is inserted at module translation. The translation further implements an approach to wrap RTL to TLM interfaces so that the translated module can be connected to a system-level simulator. The power analysis is based on a statistical model of the underlying HW structure and an analysis of input data. The flexibility of the C++ syntax is exploited, to integrate the power evaluation technique. The accuracy and speed-up of the approach are illustrated and compared to a conventional power analysis flow using PPR simulation, based on Xilinx technology.